Mrs. Job - Affinito, Mona Gustafson (iUniverse Inc, 2009)
"Beautiful, feisty Dara, rising from nomad to princess, experiences joy, spiritual and marital conflict, and unspeakable trials, without surrendering her love for Job and for her best friend Adah"–p. 4 of Cover.
Keywords: Christianity; Fiction; Religious fiction; American; Fiction; Suffering; Fiction; Wives; Job (Biblical figure); Religious aspects; dept.psy; faculty_collection

The Tragedy of Child Care in America - Zigler, Edward; Marsland, Katherine W.; Lord, Heather (Yale University Press, 2009)
Why the United States has failed to establish a comprehensive high-quality child care program is the question at the center of this book. Edward Zigler has been intimately involved in this issue since the 1970s, and here he presents a firsthand history of the policy making and politics surrounding this important debate. Good-quality child care supports cognitive, social, and emotional development, school readiness, and academic achievement. This book examines the history of child care policy since 1969, including the inside story of America's one great attempt to create a comprehensive system of child care, its failure, and the lack of subsequent progress. Identifying specific issues that persist today, Zigler and his coauthors conclude with an agenda designed to lead us successfully toward quality care for America's children. © 2009 by Yale University. All rights reserved.
Keywords: Child care; Government policy; Services for; United States; United States; Child welfare; United States; Children; dept.psy; faculty_collection

Words that predict outstanding performance - Abe, Jo Ann A. (Journal of Research in Personality, 2009)
This study applied word count strategies developed by expressive writing researchers to examine whether the words students use to describe and reflect on their field practicum experiences would predict practicum supervisors' ratings of their performance. The weekly journals of 66 students who completed a practicum at a mental health or school setting were analyzed using a computerized text-analysis program. As expected, positive emotion words and "insight" words were positively correlated with almost all dimensions of evaluation, with the exception of organizational ability, and "we" words were associated with dimensions that focused on interpersonal relations. These findings further support the view that positive emotion words and "insight" words are powerful markers of cognitive broadening and behavioral flexibility and that "we" words index feelings of affiliation and belonging. As one might expect, there was an increase in "we" words and a decrease in "anxiety" words over the course of the internship. © 2009 Elsevier Inc. All rights reserved.
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00125 tex.type: [object Object]
Keywords: Experiential learning; Positive emotions; Reflection; Text-analysis; dept.psy; peer-reviewed

Delay-amount tradeoffs in choices by pigeons and rats: hyperbolic versus exponential discounting. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2009)
An adjusting-delay procedure was used to study the choices of pigeons and rats when both delay and amount of reinforcement were varied. In different conditions, the choice alternatives included one versus two reinforcers, one versus three reinforcers, and three versus two reinforcers. The delay to one alternative (the standard alternative) was kept constant in a condition, and the delay to the other (the adjusting alternative) was increased or decreased many times a session so as to estimate an indifference point–a delay at which the two alternatives were chosen about equally often. Indifference functions were constructed by plotting the adjusting delay as a function of the standard delay for each pair of reinforcer amounts. The experiments were designed to test the prediction of a hyperbolic decay equation that the slopes of the indifference functions should increase as the ratio of the two reinforcer amounts increased. Consistent with the hyperbolic equation, the slopes of the indifference functions depended on the ratios of the two reinforcer amounts for both pigeons and rats. These results were not compatible with an exponential decay equation, which predicts slopes of 1 regardless of the reinforcer amounts. Combined with other data, these findings provide further evidence that delay discounting is well described by a hyperbolic equation for both species, but not by an exponential equation. Quantitative differences in the y-intercepts of the indifference functions from the two species suggested that the rate at which reinforcer strength decreases with increasing delay may be four or five times slower for rats than for pigeons.
71 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Long Evans rat; Male; Models; Psychological; Rats; Rats; Long-Evans; Reinforcement Schedule; Reward; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; psychological model; rat; reinforcement; reward

Re-examining the long-term effects of experiencing parental death in childhood on adult psychopathology. - Jacobs, John R; Bovasso, Gregory B (Journal of Nervous and Mental Disease, 2009)
This study examined whether the experience of the death of a parent in childhood increases risk for adult psychopathology. Participants consisted of 3481 men and women gathered through the Baltimore Epidemiologic Catchment Area study in 1981 and followed through 1994-1995. The Diagnostic Interview Survey was administered by trained interviewers and was used to assess DSM-III disorders including major depression, panic, and anxiety disorders. Maternal death was not a predictor of adult psychopathology. The death of the father during childhood more than doubled the risk for major depressive disorder in adulthood. This study did not find any significant interactions between gender of the deceased parent and gender of the participant nor did the current age of the participant or their age at the time of the death of a parent affect risk for adult psychopathology. The long-term effect on adult depression of the experience of the death of the father in childhood is attributed to likely financial stresses, which may have continued for years and possibly into early adulthood, complicating the family's adaptation to the initial loss.
34 citations (Crossref) [2023-10-31] Place: United States Jacobs, John R. Department of Psychology, Southern Connecticut State University, New Haven, Connecticut, USA. jacobsj1@southernct.edu
Keywords: *Bereavement; *Death; *Mental Disorders/et [Etiology]; *Mental Disorders/px [Psychology]; *Parents; *Psychology; Child; Anxiety Disorders; Anxiety Disorders/di [Diagnosis]; Anxiety Disorders/et [Etiology]; Anxiety Disorders/px [Psychology]; Bereavement; Child Psychology; Death; Depression; Depressive Disorder; Major; Depressive Disorder; Major/di [Diagnosis]; Depressive Disorder; Major/ep [Epidemiology]; Depressive Disorder; Major/et [Etiology]; Depressive Disorder; Major/px [Psychology]; Diagnostic and Statistical Manual of Mental Disorders; Economics; Fathers; Female; Humans; Incidence; Male; Mental Disorders; Middle Aged; Mothers; Panic; Parental death; Parents; Prevalence; Risk Factors; Stress; Psychological; Stress; Psychological/et [Etiology]; Time Factors; adaptive behavior; adult; adulthood; anxiety disorder; article; bereavement; child psychology; childhood; death; depression; dept.psy; diagnostic and statistical manual of mental disorders; economics; family stress; father; female; gender; human; incidence; interview; major depression; male; maternal mortality; mental disease; mental stress; middle aged; mother; normal human; panic; parent; parental deprivation; personal experience; prevalence; psychological aspect; risk factor; time; time of death

Training in assessment criteria indicative of deception to improve credibility judgments - Colwell, Kevin; Hiscock-Anisman, Cheryl; Memon, Amina; Colwell, Lori H.; Taylor, Laura; Woods, Debra (Journal of Forensic Psychology Practice, 2009)
The recent attention given to false confessions and convictions underscores the need for a valid and applicable system of credibility assessment. The current study demonstrates the effectiveness of assessment criteria indicative of deception (ACID) training in increasing rater's ability to discriminate between honest and deceptive transcripts. ACID generates credibility assessment through analysis of behaviors related to memory and impression-management as they occur during the course of an investigative interview. Raters were taught that honest responses are longer, more vivid, and more spontaneous than deceptive responses. Conversely, deceptive responses are shorter, less vivid, more rigid, more carefully phrased, and less likely to change during the course of an investigative interview. Trained raters were able to correctly identify 77% of transcripts as honest or deceptive, whereas untrained raters correctly identified 57%. Future research should focus on using the ACID technique in more realistic situations and should involve training of professional investigators.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/078-923-743-395-732 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Credibility; Detecting deception; Investigative interviewing; accuracy; analytic method; article; assessment criteria indicative of deception; behavioral research; controlled study; criminal justice; decision making; dept.psy; honesty; human; interview; self evaluation; training